Consumer Perceptions of Drug Safety and Effectiveness in Digital Self-Medication Practices: A Systematic Literature Review - Ahmad Azrul Zuniarto; Lia Natalia; Ajeng Hanugrahing Dewi (Jurnal Ners, 2026)
The rapid expansion of digital pharmacy platforms has intensified online self-medication practices globally, yet consumer perceptions of drug safety and effectiveness through digital channels remain poorly understood existing reviews examine these dimensions separately without an integrated framework. This qualitative Systematic Literature Review (SLR), conducted following PRISMA 2020 guidelines, synthesises evidence from 31 studies identified across Scopus, PubMed, and Google Scholar (2021-2026). Eligibility was determined using the SPIDER framework; two independent reviewers performed selection (Cohen's κ = 0.87); and data were synthesised using three-stage thematic synthesis. On the safety dimension, 12 indicators were identified across 61 coded instances: 80.3% reported negative impacts, dominated by information transparency deficits (F=19), difficulty distinguishing licensed from illegal platforms (F=14), and absence of pharmacist interaction (F=4). On the effectiveness dimension, all six indicators (11 instances) were exclusively negative, including low medication literacy (F=4), drug interaction risks (F=2), self-diagnosis inaccuracy (F=2), and elevated adverse drug reaction rates. Negative perceptions across both dimensions consistently stem from three structural determinants: weak regulatory frameworks, low medication literacy, and the structural absence of professional oversight. Multi-level interventions are urgently needed, encompassing platform regulation standardisation, digital health literacy promotion, and mandatory pharmacist consultation integration.